Eurycleonus talamellii n. sp. of Cleonine weevil from the Moroccan desert (Coleoptera: Curculionidae: Lixinae: Cleonini) - Meregalli, Massimo (Zootaxa, 2005)
Eurycleonus talamellii n. sp. is described. It is a taxonomic and geographic vicariant of E. gigas (Marseul 1868), from which it mainly differs by the body with less broadened elytra, the vestiture composed of mixed white and brownish scales in irregular patches, the rostrum nearly straight in profile, the antennae with slightly longer segments, the upper margin of the scrobe sinuate and nearly reaching the lower part of the eye. Remarks on ecology, biogeography and phylogenetic relationships are given.Kew words: Curculionidae, Eurycleonus, Eurycleonus talamellii, new species, taxonomy, biogeography, host plants, Morocco